Simultaneous concurrent chemoradiotherapy and esophagectomy for synchronous head and neck and esophageal squamous cell carcinoma: a retrospective review - Yu-Ming Huang; Yi-Shing Leu; Jehn-Chuan Lee; Chao-Hung Chen; Hung-Chang Liu; Chih-Hao Chen; Huan-Chau Lin; Nai-Wen Su; Wen-Chien Huang; Yu-Jen Chen (Radiation Oncology)
Abstract Background This study aimed to assess the clinical outcomes and prognostic factors of patients with synchronous head and neck squamous cell carcinoma (HNSCC) and esophageal squamous cell carcinoma (ESCC) who underwent simultaneous concurrent chemoradiotherapy (CCRT) and esophagectomy. Methods Thirty-one patients who underwent simultaneous CCRT for synchronous HNSCC and ESCC were retrospectively reviewed. The treatment strategy involved simultaneous definitive CCRT at 70 Gy/35 fractions for HNSCC and neoadjuvant CCRT at 48 Gy/24 fractions for ESCC. Esophagectomy was evaluated 4–5 weeks after neoadjuvant CCRT. The radiotherapy plan utilized a simultaneously integrated boost technique at 4–5 dose levels. Patients received weekly platinum chemotherapy during CCRT. Patient characteristics, treatment responses, and survival rates were analyzed. Survival analysis was conducted using the Kaplan–Meier method and Cox regression analyses. Results All the patients completed CCRT at the planned doses and radiation fields with a good tolerance profile. The 1- and 2-year survival rates were 62.9% and 34.4%, respectively. Performance status (PS), ESCC tumor location, HNSCC clinical stage, and clinical responses of HNSCC and ESCC, both individually and combined, were significantly associated with prognosis. PS and the clinical response of ESCC were significant predictors of overall survival. Adverse effects were manageable, with up to eleven patients (35.5%) developing grade 3/4 neutropenia. No treatment-related mortality was noted. Conclusions The treatment strategy using simultaneous definitive CCRT for HNSCC and neoadjuvant CCRT for ESCC followed by esophagectomy for synchronous HNSCC and ESCC is effective and well-tolerated. PS and clinical response of ESCC are significant prognostic factors for this treatment strategy.